MEMPERKENALKAN CODING ARDUINO UNTUK SISWA SMPIT HARAPAN MULIA PALEMBANG - Nyayu Latifah Husni; Iskandar Lutfi; Amperawan Amperawan; Masayu Anisah; Ade Silvia Handayani (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
Coding is really needed nowadays. It is because of the high need for coding in every fields. The science of coding has brought people to a world that is completely automated and easy. Due to the need for this coding, many people start to learn it as early as possible.  The activity that is held at SMPIT Harapan Mulia in 2020 is the continuation of the 2019 Community Service, where in 2019, the team conducted the training of introducing garbage robot control based on iPad at SMPIT Harapan Mulia Palembang. The training impressed students and teachers very much. Thus, They felt happy and interested in learning more about programming sciences (coding). This prompted them to ask the service team to return to their school to conduct another training. The participants (students of SMPIT Harapan Mulia) were very enthusiastic about participating in the counseling and training.